Pulmonary Localization Revealing Wegener's Granulomatosis - Mona Mlika; Aida Ayadi-Kaddour; Adel Marghli; Tarek Kilani; Faouzi El Mezni (The Scientific World Journal)
Wegener's granulomatosis (WG) is the most frequent antineutrophil cytoplasmic antibody (ANCA)–associated vasculitis. It affects mainly the upper airways, lungs, and kidneys. Two forms are identified: systemic and limited. We describe three cases of limited WG diagnosed during a 7-year period. Our aim is to report three localized forms of WG and to put emphasis on the necessity of differentiating localized from systemic forms because of their different prognoses and manner of management. Our study contained two men and one woman with a mean age of 43 years. All our patients were symptomatic and presented with nonspecific respiratory signs. The cANCA were positive in all patients. The imaging findings consisted of cavitary masses. The diagnosis was based on surgical lung biopsy in all cases. All patients were put on cyclophosphamide and prednisolone. Only one patient presented with renal complications after a 2-year follow-up period. The two other patients did not present complications after, respectively, 1 month and 1 year of follow-up. These case reports put emphasis on a rare form of WG, the limited form. The low number of patients, due to the rarity of this disease, does not allow us to delineate the characteristics and the differences between this form and the systemic form, but we highlight the necessity of future investigations in order to explore the pathogenesis, therapeutic, and prognosis differences between these two subsets.